Answer:
y = 3x - 6
y + 3 = 3(x - 1)
Explanation:
Slope-Intercept Form: y = mx + b
Point-Slope Form: y - y₁ = m(x - x₁)
Slope Formula:
![m=(y_2-y_1)/(x_2-x_1)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/e9lgdayfzr27dyurvzbw9lffpiv7535tiv.png)
Step 1: Find slope m
![m=(15-(-3))/(7-1)](https://img.qammunity.org/2021/formulas/mathematics/high-school/ztpdzt9mfxm336ouv93xmtc45g31ep1xgj.png)
![m=(15+3)/(6)](https://img.qammunity.org/2021/formulas/mathematics/high-school/6sunefnn2y66icr4wu9403mamchga7es6h.png)
![m=(18)/(6)](https://img.qammunity.org/2021/formulas/mathematics/high-school/a80esiufg90bxto7g0segtcoawquyorqhq.png)
![m=3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/1gd7netuxdn1rni2nn5jlsja6h6py5j1k1.png)
y = 3x + b
Step 2: Find y-intercept b
-3 = 3(1) + b
-3 = 3 + b
b = -6
Step 3: Write linear equation
y = 3x - 6
or
y + 3 = 3(x - 1)